Ischemia in intracerebral hemorrhage: A comparative study of small‐vessel and large‐vessel diseases. Issue 1 (12th January 2022) - Zhang, Ailing; Ren, Mengyang; Deng, Wenjing; Xi, Meijing; Tian, Long; Han, Zhuoya; Zang, Weiping; Hu, Hao; Zhang, Bin; Cui, Ling; Qi, Peihong; Shang, Yingjie
Abstract: Objective: This study aimed to compare effects of cerebral small‐vessel disease (cSVD) burden and cerebral artery stenosis (CAS) on acute ischemia in intracerebral hemorrhage (ICH) and their interaction with mean arterial pressure (MAP) change. Methods: We recruited consecutive patients with acute primary ICH. Brain magnetic resonance imaging and angiography were performed to quantify diffusion‐weighted imaging (DWI) lesions, CAS, and cSVD markers, which were calculated for the total cSVD score. Multivariable regression models were adopted to explore their associations by DWI lesions size (<15 vs. ≥15 mm) and median MAP change stratification. Results: Of 305 included patients (mean age 59.5 years, 67.9% males), 77 (25.2%) had DWI lesions (small, 79.2%; large, 20.8%) and 67 (22.0%) had moderate and severe CAS. In multivariable analysis, small DWI lesions were independently associated with higher total cSVD score (odds ratio [OR] 1.81, 95% confidence interval [CI] 1.36–2.41). and large DWI lesions were associated with more severe CAS (OR 2.51, 95% CI 1.17–5.38). This association was modified by MAP change (interaction p = 0.016), with stratified analysis showing an increased risk of large DWI lesions in severe CAS with greater MAP change (≥44 mmHg) (OR 3.48, 95% CI 1.13–10.74) but not with mild MAP change (<44 mmHg) (OR 1.21, 95% CI 0.20–7.34). Interpretation: Total cSVD burden is associated with small DWI lesions, whereas the degree of CAS is associated with large DWI lesions, specifically with greater MAP change, suggesting that large‐artery atherosclerosis may be involved in ischemic brain injury, which is different from small‐vessel pathogenesis in ICH.